BANDUNG CITY GOVERNMENT ENVIRONMENT AND SANITATION SERVICE CAPACITY IN WASTE MANAGEMENT - Deden Hadi Kushendar; Kurhayadi Kurhayadi; Aep Saepudin; Muhammad Yusuf (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
Waste management is an activity carried out in an effort to handle and reduce waste which includes collection, transportation, final disposal and processing which aims to improve public health and environmental quality. The research method used in this study is a descriptive method with a qualitative approach. Data collection techniques were carried out to answer research problems, namely interviews, observation, documentation, and literature studies. To check the validity of the data, triangulation techniques were carried out, namely source triangulation, technique/method triangulation and theoretical triangulation. Based on the findings in the field, the researchers concluded that the capacity of the Bandung City Environment and Sanitation Service in waste management in Bandung City had not been maximized.